Adverse events of PD-(L)1 inhibitors plus anti-VEGF(R) agents compared with PD-(L)1 inhibitors alone for cancer patients: a systematic review and meta-analysis - Tang, Qiyu; Wu, Dawei; Huang, Huiyao; Fang, Hong; Wu, Ying; Liu, Funan; Li, Ning (Frontiers in Pharmacology, 2023)
Abstract Background: anti-PD-(L)1 antibody monotherapy or in combination with VEGF(R) blockade have been applied widely for cancer treatment. While whether the combination therapy increases irAEs still remains controversial. Methods: A systematic review and meta-analysis comparing PD-(L)1 and VEGF(R) blockades combination therapy with PD-(L)1 inhibitors alone was performed. Phase II or III randomized clinical trials reporting irAEs or trAEs were included. The protocol was registered with PROSPERO, CRD42021287603. Results: Overall, 77 articles were included in the meta-analysis. 31 studies involving 8638 participants were pooled and reported an incidence for PD-(L)1 inhibitors monotherapy with any grade and grade ≥3 irAEs of 0.25 (0.20, 0.32), 0.06 (0.05, 0.07), respectively. 2 studies with 863 participants were pooled for PD-(L)1 and VEGF(R) blockades showed an incidence of any grade and grade ≥3 irAEs were 0.47 (0.30, 0.65), 0.11 (0.08, 0.16), respectively. Regarding pairwise comparisons for irAEs, only one study was included, indicating no significant difference between the two regimens in terms of colitis, hyperthyroidism, hypothyroidism for any grade and grade ≥3, while there was a trend of higher incidence for any grade hyperthyroidism under the combination therapy. Incidence of reactive cutaneous capillary endothelial proliferation (RCCEP) was as high as 0.80 under camrelizumab monotherapy. Conclusions: Total incidences of any grade and grade ≥3 irAEs were higher in the combination treatment group. Direct comparisons indicated no significant difference between the two regimens for any grade and grade ≥3 specific irAEs. RCCEP and thyroid disorders need be paid attention to clinically. Moreover, trials with direct comparisons are needed and safety profiles of the two regimens should be further explored. Exploration of mechanism of action and regulatory managements of adverse events should be enhanced.